2021
DOI: 10.1101/2021.12.13.472487
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanoscale details of mitochondrial fission revealed by cryo-electron tomography

Abstract: Mitochondrial fission is required for proper segregation during cell division, quality control, and cellular homeostasis (metabolism and energy production). Despite its importance, models of the process remain speculative. Here we apply cryogenic electron tomography to image the nanoscale architecture of mitochondrial fission in mammalian cells. We find that constriction of the inner and outer membranes is coordinated, suggesting that force on both membranes is applied externally. While we observe ER at constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…Work has shown that ARTS acts as a scaffold to bring XIAP into close proximity with anti-apoptotic Bcl-2 and promote its degradation (Edison et al, 2017). Considering work from our lab and others (Krokowski et al, 2018;Lobato-Márquez et al, 2021;Mageswaran et al, 2021;Mostowy et al, 2010;Pagliuso et al, 2016;Sirianni et al, 2016) it is tempting to speculate that septins (including SEPT7 and SEPT2, but not ARTS) are recruited to mitochondrial constriction sites that present micron-scale curvature. Here, septins may function as a scaffold to recruit Drp1 to mitochondrial fission sites (in healthy cells) or apoptotic foci (in apoptotic cells), and promote interactions of Drp1 with other proteins involved in MOMP (e.g., Bax).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Work has shown that ARTS acts as a scaffold to bring XIAP into close proximity with anti-apoptotic Bcl-2 and promote its degradation (Edison et al, 2017). Considering work from our lab and others (Krokowski et al, 2018;Lobato-Márquez et al, 2021;Mageswaran et al, 2021;Mostowy et al, 2010;Pagliuso et al, 2016;Sirianni et al, 2016) it is tempting to speculate that septins (including SEPT7 and SEPT2, but not ARTS) are recruited to mitochondrial constriction sites that present micron-scale curvature. Here, septins may function as a scaffold to recruit Drp1 to mitochondrial fission sites (in healthy cells) or apoptotic foci (in apoptotic cells), and promote interactions of Drp1 with other proteins involved in MOMP (e.g., Bax).…”
Section: Discussionmentioning
confidence: 86%
“…Work has shown that ARTS acts as a scaffold to bring XIAP into close proximity with anti-apoptotic Bcl-2 and promote its degradation (Edison et al, 2017). Considering work from our lab and others (Krokowski et al, 2018;Lobato-Márquez et al, 2021;Mageswaran et al, 2021;Mostowy et al, 2010;Pagliuso et al, 2016;Sirianni et al, 2016) it is tempting to speculate that septins (including SEPT7 and SEPT2, but not…”
Section: Testing the Role Of Septin-mediated Apoptosis During S Flexn...mentioning
confidence: 88%
“…Recently, quantitative analyses of membrane thickness and curvature have been the key to holistically understand biological processes as mitochondrial and bacterial division in cryo-FIB milled cellular samples. Constriction stages in mitochondrial division were identified based on membrane curvature and proximity to different cytoskeletal filaments that ultimately help fission ( Mageswaran et al, 2021 ). Vectorization of cytoskeletal elements served to distinguish different populations of filaments based on thickness: actin, microtubules and septin filaments ( Rigort et al, 2012 ).…”
Section: Quantitative Cryo-electron Tomographymentioning
confidence: 99%
“…Vectorization of cytoskeletal elements served to distinguish different populations of filaments based on thickness: actin, microtubules and septin filaments (Rigort et al, 2012). Further analysis of the filament populations within tomograms of wild-type vs. knock down Sept2 protein cells help identify the role of each filament since positioning and interactions can be then related to each division stage (Mageswaran et al, 2021). In bacteria, different division stages were established based on inner membrane closure distances measured in many dividing wild-type and cell wall biogenesis mutants.…”
Section: Case Examplesmentioning
confidence: 99%
“…Higgs and colleagues suggest this Ca 2+ uptake and IMM constriction is promoted by ER-localized INF2 mediating actin polymerization after Ca 2+ release by the ER, causing increased proximity of the ER and mitochondria. However, a recent preprint using cryo-EM analysis to characterize mitochondrial division sites in unprecedented detail has suggested that IMM constriction is simultaneous with OMM constriction, begging the question of whether an IMM machinery is necessary to coordinate the process ( Mageswaran et al, 2021 ).…”
Section: The Interplay Between Mitochondrial Dynamics and Mitochondri...mentioning
confidence: 99%